Strategi dan Kebijakan untuk Mewujudkan Keadilan Ekonomi dalam Distribusi Hasil Pertanian Perspektif Ekonomi Islam - Lestari Nst, Listika Putri Ayu; Nurbaiti, Nurbaiti; B Syarbaini, Ahmad Muhaisin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The agricultural sector in Medan City holds significant potential to contribute to the national economy through high employment absorption and substantial foreign exchange earnings from agribusiness. Although agricultural products such as rice, corn, and soybeans play a vital role in meeting local food needs and increasing farmers' income, the distribution of these products still faces challenges related to inequality. This study aims to explore the effectiveness of agricultural product distribution in Medan City, focusing on existing distribution channels, including traditional markets and modern retail outlets. This research adopts a qualitative approach with a total of 30 respondents, consisting of farmers, traders, and academics. The data analysis technique used is thematic analysis to understand the dynamics of distribution and economic justice within the framework of Islamic economics. The findings reveal that inequality in access to resources and price disparities between farmers and consumers remain major issues. Moreover, factors such as distribution infrastructure and government policies significantly influence the efficiency of distribution. This study recommends improvements in the distribution system, including strengthening infrastructure and providing support for local farmers, to achieve a more just and sustainable distribution of agricultural products. Ultimately, these efforts are expected to ensure more equitable welfare for both farmers and consumers while promoting a justice-based economic model at both local and national levels.